2007
DOI: 10.1111/j.1467-9280.2007.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal Smells can Guide Social Preferences

Abstract: ABSTRACT-It is widely accepted that unconscious processes can modulate judgments and behavior, but do such influences affect one's daily interactions with other people? Given that olfactory information has relatively direct access to cortical and subcortical emotional circuits, we tested whether the affective content of subliminal odors alters social preferences. Participants rated the likeability of neutral faces after smelling pleasant, neutral, or unpleasant odors delivered below detection thresholds. Odor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
169
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(184 citation statements)
references
References 30 publications
10
169
0
1
Order By: Relevance
“…Perhaps, the influence of olfactory cues on emotion is unconscious as shown by Li et al (2007) who found an effect of scent on the likability rating of faces only for participants lacking conscious awareness of the scent.…”
Section: Are Sensory Modalities Linked To Assessment Perspectives or mentioning
confidence: 99%
“…Perhaps, the influence of olfactory cues on emotion is unconscious as shown by Li et al (2007) who found an effect of scent on the likability rating of faces only for participants lacking conscious awareness of the scent.…”
Section: Are Sensory Modalities Linked To Assessment Perspectives or mentioning
confidence: 99%
“…Odors may communicate emotional information such as disgust and fear (de Groot, Smeets, Kaldewaij, Duijndam, & Semin, 2012), and perception of body odors may guide social preferences (Li, Moallem, Paller, & Gottfried, 2007). Odors are particularly potent in evoking disgust, and disgust is the primary emotional response to unpleasant odors (Alaoui-Ismaïli, Robin, Rada, Dittmar, & Vernet-Maury, 1997;AlaouiIsmaïli, Vernet-Maury, Dittmar, Delhomme, & Chanel, 1997).…”
mentioning
confidence: 99%
“…Overall, these results are in accord with the hypothesis that a task-irrelevant motion direction presented in the background was misattributed as task-relevant information for preferential decisionmaking. As indicated in §1, previous studies have concentrated on misattribution that originates in cognitive stages, including those that process emotion [1,2], mood [4] and past choice [3]. However, the results of the present experiment suggest that misattribution can also originate in a visuomotor interaction stage.…”
Section: Results and Discussion (A) Experimentsmentioning
confidence: 48%